Zebrafish as a Model System to Study the Mechanism of Cutaneous Wound Healing and Drug Discovery: Advantages and Challenges - Ruth Naomi; Hasnah Bahari; Muhammad Dain Yazid; Hashim Embong; Fezah Othman (MDPI AG, 2021)
In humans, cutaneous wounds may heal without scars during embryogenesis. However, in the adult phase, the similar wound may undergo a few events such as homeostasis, blood clotting, inflammation, vascularization, and the formation of granulation tissue, which may leave a scar at the injury site. In consideration of this, research evolves daily to improve the healing mechanism in which the wound may heal without scarring. In regard to this, zebrafish (Danio rerio) serves as an ideal model to study the underlying signaling mechanism of wound healing. This is an important factor in determining a relevant drug formulation for wound healing. This review scrutinizes the biology of zebrafish and how this favors the cutaneous wound healing relevant to the in vivo evidence. This review aimed to provide the current insights on drug discovery for cutaneous wound healing based on the zebrafish model. The advantages and challenges in utilizing the zebrafish model for cutaneous wound healing are discussed in this review. This review is expected to provide an idea to formulate an appropriate drug for cutaneous wound healing relevant to the underlying signaling mechanism. Therefore, this narrative review recapitulates current evidence from in vivo studies on the cutaneous wound healing mechanism, which favours the discovery of new drugs. This article concludes with the need for zebrafish as an investigation model for biomedical research in the future to ensure that drug repositions are well suited for human skin.